2006
DOI: 10.1515/jpem.2006.19.5.691
|View full text |Cite
|
Sign up to set email alerts
|

Hypothalamo-hypophysial Dysfunction After Traumatic Brain Injury in Children and Adolescents: A Preliminary Retrospective and Prospective Study

Abstract: With two study protocols, one retrospective and the other prospective, we evaluated hypothalamo-hypophysial dysfunction (HHD) in paediatric patients treated for traumatic brain injury (TBI) in the neurosurgical or intensive care department at our hospital. The retrospective group comprised 22 patients who had experienced TBI 0.7-7.25 years before the study. The prospective group included 30 patients assessed at TBI (T0), 26 of 30 after 6 months (T6), and 20 of 26 after 12 months (T12). Auxological and hormonal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
104
4
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(113 citation statements)
references
References 14 publications
4
104
4
1
Order By: Relevance
“…Pituitary deficiency has been reported after severe brain trauma, often associated not only with loss of consciousness, subdural haematoma or skull fracture (26)(27)(28)(29), but also following relatively mild head injury without loss of consciousness (30)(31)(32). A recent preliminary retrospective and prospective analysis of paediatric and adolescent patients also confirmed the risk of pituitary dysfunction (33).…”
Section: Evidence For Abnormal Pituitary Function After Tbi In Childrmentioning
confidence: 92%
“…Pituitary deficiency has been reported after severe brain trauma, often associated not only with loss of consciousness, subdural haematoma or skull fracture (26)(27)(28)(29), but also following relatively mild head injury without loss of consciousness (30)(31)(32). A recent preliminary retrospective and prospective analysis of paediatric and adolescent patients also confirmed the risk of pituitary dysfunction (33).…”
Section: Evidence For Abnormal Pituitary Function After Tbi In Childrmentioning
confidence: 92%
“…Pituitary hormone secretion is regulated by hypothalamic-releasing hormones and inhibitory factors (which are released into the portal circulation in the pituitary 10,11,13,26 to avoid the confounding effect of acute critical illness on neuroendocrine function and studies on pediatric populations for reasons of homogeneity 24,25 ). Of these, the pooled prevalences of anterior hypopituitarism after TBI and aneurysmal SAH were 27.5% (95% CI, 22.8%-28.9%) and 47% (95% CI 37.4%-56.8%), respectively.…”
Section: Prevalence Of Anterior Hypopituitarism After Tbi and Sahmentioning
confidence: 99%
“…[4][5][6][7][8] Previous prospective studies have often found resolution of some endocrine abnormalities by 1 year after TBI. For this reason, we elected to only study children who were at least 1 year after injury.…”
Section: Discussionmentioning
confidence: 99%
“…However, few studies have systematically evaluated the prevalence of endocrine dysfunction in children after TBI. [4][5][6][7][8] Among studies in children, there is a 16-61% prevalence of hypopituitarism at 1-5 years after injury. [4][5][6][7][8] Two studies with prospective data in the pediatric age range have shown an incidence of 10 4 and 29% 8 pituitary deficiency at 1 year after injury.…”
Section: Introductionmentioning
confidence: 99%